2012
DOI: 10.1111/j.1447-0756.2012.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gestational age in twin pregnancy: Which fetal crown–rump length should be used?

Abstract: The smaller CRL is more accurate in the estimation of the GA for twin pregnancy compared to the larger or mean CRL values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Other studies have recommended the use of the smaller CRL or the mean CRL, which takes into account both fetuses. The disadvantage of using the smaller CRL is the potential of the operator believing that the larger twin is large‐for‐gestational age, and therefore being falsely reassured that the smaller twin is still growing appropriately.…”
Section: Recommendationsmentioning
confidence: 99%
“…Other studies have recommended the use of the smaller CRL or the mean CRL, which takes into account both fetuses. The disadvantage of using the smaller CRL is the potential of the operator believing that the larger twin is large‐for‐gestational age, and therefore being falsely reassured that the smaller twin is still growing appropriately.…”
Section: Recommendationsmentioning
confidence: 99%
“…Studies on twin gestations conceived by assisted reproduction have demonstrated that the smaller CRL is a more accurate estimate of the true gestational age in twins, specifically when there is less than 95% discrepancy in CRL. 5,6 Other studies suggest that accurate dating can be obtained by averaging the gestational age of each fetus. 7 However, most experts agree that dating in a twin pregnancy should be based on the larger fetus to avoid missing early intrauterine growth restriction of the cotwin.…”
Section: Determining Gestational Agementioning
confidence: 98%
“…Twin pregnancies are dated according to the crown–rump length (CRL) measurement in the larger twin at the 11 + 0 to 13 + 6‐week scan 11 . Some studies suggested that the CRL of the smaller twin may be more accurate 115 but, as this can give false reassurance that the smaller twin is growing appropriately, leading to a missed diagnosis of aneuploidy or sFGR, this method is not commonly used in practice.…”
Section: Timing Of Birth In Uncomplicated Twin Pregnancymentioning
confidence: 99%